Respuesta :

Answer:

[tex]y = - x-1[/tex]

Step-by-step explanation:

The line a passes through th points (-1,0) and (0,-1)

The equation of line which is passes through the point [tex](x_1,y_1)[/tex] and [tex](x_2,y_2)[/tex] is

[tex](y-y_1)= \frac{y_2-y_1}{x_2-x_1} (x-x_1)[/tex]

Therefore the equation of line which passes through the points (-1,0) and (0,-1)

is

[tex]y-0=\frac{-1-0}{0-(-1)} [x-(-1)][/tex]       [ [tex]x_1 = -1, y_1= 0[/tex] [tex]x_2 = 0[/tex]  and [tex]y_2 = -1[/tex]]

[tex]\Leftrightarrow y = -1 (x+1)[/tex]

[tex]\Leftrightarrow y = - x-1[/tex]

Answer:

b

Step-by-step explanation:

ACCESS MORE